The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1097/00006324-200004000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Corneal Asphericity in Myopia

Abstract: These data show a shift to a more positive Q (in the oblate direction) with increased myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
4
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 22 publications
3
40
4
3
Order By: Relevance
“…In previous studies, anterior corneal surface asphericity showed variation in different types of ametropia. Myopes were more oblate and hyperopes were more prolate [20,21]. Contrasting these results, some studies show no significant correlation between corneal surface asphericity and spherical equivalence [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, anterior corneal surface asphericity showed variation in different types of ametropia. Myopes were more oblate and hyperopes were more prolate [20,21]. Contrasting these results, some studies show no significant correlation between corneal surface asphericity and spherical equivalence [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…They reported P values of 0.88 for emmetropes and 0.89 for hyperopes and myopes (Q value À0.12 and À0.11, respectively). Carney et al 25 (r 2 Z 0.076, P Z .0045) and Horner et al 26 (r 2 Z 0.08, P!.05) found a trend toward more positive Q values as the level of myopia increased. Mainstone et al 27 (r 2 Z 0.003, P Z .742), Atchison 28 (r 2 Z À0.008, P Z .962), and Budak et al 29 (P Z .208) found no relationship between corneal asphericity and refractive error.…”
Section: Corneal Surfaces In the Study Populationmentioning
confidence: 90%
“…El RC se obtuvo del mapa queratométrico, mientras que Q se calculó en la zona de 4,5 mm usando el Holladay Diagnostic Summary (4). En ambos casos el valor final se corresponde al promedio de tres medidas.…”
Section: Procedimientosunclassified
“…Existen numerosos estudios (longitudinales, trasversales y epidemiológicos) que tratan de ampliar los conocimientos sobre el desarrollo y progresión de los errores refractivos, centrándose en la relación entre los componentes oculares, la topografía corneal y en su papel en el desarrollo de la ametropía (1)(2)(3)(4). De la misma forma, también han cobrado interés las implicaciones en cirugía refractiva (5-7) o en la calidad óptica del ojo (8).…”
Section: Introductionunclassified